Điều tra sản phẩm và phụ phẩm nông nghiệp sử dụng làm nguồn chất xơ cho gia súc nhai lại tại tỉnh Phitsanulok, Thái Lan - .Laorodphan, N; Sangseeda, T.; Sang-arun, D.; Tepsutin, L.; Yaemkong, S.; Rattanapradit, P. (Tạp chí Khoa học Nông nghiệp Việt Nam, 2025)
The purposes of this research were to explore the source of product and by-product from agricultural and to evaluate chemical composition of agricultural by-product in Muang Phitsanulok (MP), Nern-Maprang (NM) and Nakhon-Thai (NT) districts, Phitsanulok Province. The purposive samples used by a questionnaire and surveying were 362 farmers. The data was statistically analysed by using a linear model that considered all factors as fixed effects. Least squares means for subclasses of each factor were estimated and they were compared using t-tests. In addition, the agricultural product and by-product were collected from surveying area and was analysed for chemical composition by AOAC method. The results revealed that cultivating area (CA), average yield (AY), and average by-product (AP) were affected by farm location-source of by-product (p > 0.01). Farmers from MP district had the higher CA, AY, and AP from rice than NT and NP districts, respectively, except for CA from NP and NT districts, respectively. In contrast farmers from NP district had higher AY, and AP from corn than NT and MP districts, respectively, except for CA from NT district. Chemical analysing results showed that the chemical composition of corn stover, corn foliage and rice straw consisted of dry matter 77.58%, 94.00%, and 97.20%; ash 7.40%, 14.05%, and 13.28%; crude protein 6.32%, 3.10%, and 5.06%; crude fat 1.82%, 2.15%, and 2.39%; and crude fiber 22.87%, 24.90%, and 34.09%, respectively. These results implied that the improvement of average yield and yield and quality of by-products from agricultural in different farm locations and sources require the different strategy.